Identification of excitons, trions and biexcitons in single‐layer WS2. Issue 8 (27th July 2015) - Plechinger, Gerd; Nagler, Philipp; Kraus, Julia; Paradiso, Nicola; Strunk, Christoph; Schüller, Christian; Korn, Tobias
<x xml:space="preserve">Abstract</x> Single‐layer WS2 is a direct‐gap semiconductor showing strong excitonic photoluminescence features in the visible spectral range. Here, we present temperature‐dependent photoluminescence measurements on mechanically exfoliated single‐layer WS2, revealing the existence of neutral and charged excitons at low temperatures as well as at room temperature. By applying a gate voltage, we can electrically control the ratio of excitons and trions and assert a residual n‐type doping of our samples. At high excitation densities and low temperatures, an additional peak at energies below the trion dominates the photoluminescence, which we identify as biexciton emission. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)